Mitigating Turnover Intention Among Generation Z Employees: Work-Life Balance, Career Development, and the Mediating Role of Work Engagement - Defri Triana; Agung Nugroho Adi (Journal Research of Social Science, Economics, and Management, 2026)
Generation Z employees are more likely than previous generations to change jobs frequently and within shorter time frames, partly because they place greater emphasis on meaningful work and mental health. This explanatory quantitative study investigates the effects of work-life balance and career development on turnover intention among Generation Z employees in Greater Bandung, with work engagement examined as a mediating variable. Using purposive sampling, the study involved 139 respondents. Data were collected through an online questionnaire and analyzed with SmartPLS 3 by evaluating the measurement model, structural model, and bootstrapping results. The findings show that work-life balance and work engagement have significant negative effects on turnover intention, whereas career development has no significant direct effect on turnover intention. Work-life balance and career development also exert significant positive effects on work engagement. Furthermore, work engagement mediates the effects of both work-life balance and career development on turnover intention. These findings indicate that organizations can reduce turnover intention by strengthening work-life balance, career development, and work engagement.